EFEKTIVITAS CORE STABILITY EXERCISE TERHADAP TRUNK CONTROL PADA PASIEN STROKE : Literature Review - Zahra Adzkia Alya (2021)
Stroke is a collection of clinical signs due to disturbances in brain function. Stroke patients generally experience balance disorders, posture control, and mobilization making it difficult to carry out activities. Core stability exercise is intended to improve trunk control and balance in stroke patients. The purpose of this paper is to study the effectiveness of core stability exercise on trunk control in stroke patients on existing scientific articles. This research method is literature review. The parameter used is the trunk impairment scale (TIS), while the methodological assessment uses The Physiotherapy Evidence Database rating scale (PEDro Scale). The scientific articles used were research in the period 2016 - 2021. The results of 5 scientific articles showed a significant increase in dynamic sitting balance in the experimental group (p <0.05) compared to the control group. Which means, core stability exercise can improve trunk control in stroke patients.